HDAC10 Is Positively Associated With PD-L1 Expression and Poor Prognosis in Patients With NSCLC - Liu, Xiaomei; Wang, Yuxi; Zhang, Rong; Jin, Ting; Qu, Liangliang; Jin, Qianwen; Zheng, Jiasu; Sun, Jiaqi; Wu, Ziqing; Wang, Linxi; Liu, Tianxu; Zhang, Yinxu; et al. (Frontiers in Oncology, 2020)
Currently, non-small cell lung carcinoma (NSCLC) is remaining a major worldwide health problem. Meanwhile, accumulating evidences indicate that Histone deacetylase (HDACs) activation could induce PD-L1 expression in various types of cancer, especially in myeloma and B-cell lymphomas. Therefore, we hypothesized that high-level expression of HDAC10 is associated with PD-L1 induction and poor prognosis in patients with NSCLC. Totally, 180 NSCLC patients receiving complete pulmonary resection and systematic lymph node dissection were enrolled from April 2004 to August 2009. The patients with integrated clinicopathological records were followed up. The expression level of HDAC10 and PD-L1 in tissue samples was determined by immunohistochemistry. We observed that HDAC10 expression in lung cancer tissue is significantly higher than that in corresponding para-cancer tissue. Moreover, HDAC10 expression positively correlated with the expression level of PD-L1 (r=0.213, P<0.05) in NSCLC patients. In the subgroup, multivariate analysis showed that the expression level of HDAC10 can be an independent prognostic factor and high-level expression of HDAC10 indicated a poor overall survival in pulmonary carcinoma (r=0.540, P<0.001). Our findings suggest that the expression level of HDAC10 is positively associated with PD-L1 expression and may predict outcome of patients with NSCLC.